Well-differentiated prostate cancer in core biopsy specimens may be associated with extraprostatic disease - Cury, José; Coelho, Rafael Ferreira; Srougi, Miguel (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: Accurate determination of the Gleason score in prostate core biopsy specimens is crucial in selecting the type of prostate cancer treatment, especially for patients with well-differentiated tumors (Gleason score 2 to 4). For such patients, an inaccurate biopsy score may result in a therapeutic intervention that is too conservative. We evaluate the role of Gleason score 2-4 in prostate core-needle biopsies for predicting the fi nal pathological staging following radical prostatectomy. DESIGN AND SETTING: Retrospective study at Hospital das Clínicas, Faculdade de Medicina da Universidade de São Paulo. METHODS: We analyzed the medical records of 120 consecutive patients who underwent radical retropubic prostatectomy to treat clinical localized prostate cancer at our institution between December 2001 and July 2006. Thirty-two of these patients presented well-differentiated tumors (Gleason score 2 to 4) in biopsy specimens and were included in the study. The Gleason scores of the core-needle biopsies were compared with the pathological staging of the surgical specimens. RESULTS: Sixteen of the 32 patients (50%) presented moderately differentiated tumors (Gleason score 5 to 7) in surgical specimens. Eighteen patients (56%) had tumors with involvement of the prostate capsule and ten (31%) had involvement of adjacent organs. Evaluating the 16 patients that maintained Gleason scores of 2 to 4 in the pathological staging of the surgical specimens, 11 (68.7%) had focal invasion of the prostate capsule and fi ve (31.25%) had organ-confi ned disease. CONCLUSION: Well-differentiated tumors (Gleason score 2 to 4) seen in biopsies are not predictive of organ-confi ned disease.